2021
DOI: 10.1002/jso.26341
|View full text |Cite
|
Sign up to set email alerts
|

Pathological factors associated with non‐sentinel lymph node metastasis in early stage cervical cancer

Abstract: Objective To analyze the predictive factors for non‐sentinel lymph node (non‐SLN) metastasis in early‐stage cervical cancer. Methods We analyzed a series of 113 patients who underwent sentinel lymph node (SLN) mapping for cervical cancer. The SLNs were examined by immunohistochemistry (IHC) when the hematoxylin–eosin stain was negative. Results The overall bilateral detection rate was 81.5%, with a median of two SLNs resected. The study ultimately included 92 patients with SLNs that were mapped who had also un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
2
2
0
1
Order By: Relevance
“…Of note, a recent retrospective study including 967 patients with FIGO T1a1L1-T2b cancers found out that the size itself of the metastasis did not impact disease-free survival (DFS) (but having a (+)SLN was of course negative on DFS) [46]. On this subject, our results are consistent with those of Diniz et al and the literature [47]. These results raised the question of the specificity of lymphatic spread in cervical cancer, and we support the idea that cervical cancer spreads differently from endometrial cancer in the lymphatic system.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Of note, a recent retrospective study including 967 patients with FIGO T1a1L1-T2b cancers found out that the size itself of the metastasis did not impact disease-free survival (DFS) (but having a (+)SLN was of course negative on DFS) [46]. On this subject, our results are consistent with those of Diniz et al and the literature [47]. These results raised the question of the specificity of lymphatic spread in cervical cancer, and we support the idea that cervical cancer spreads differently from endometrial cancer in the lymphatic system.…”
Section: Discussionsupporting
confidence: 92%
“…This is most probably due to a lack of cases and, therefore, of power. Our univariate results are corroborated by Diniz's study [47]. They retained parametrial invasion as the only risk factor for positive non-SLN (p = 0.045).…”
Section: Discussionsupporting
confidence: 86%
“…Univariate analysis of risk factors for presence of low volume disease with immunohistochemistry in cervical cancer sentinel lymph nodes. of 13 patients (46%) with positive SLNs (including ITC) were detected only after IHC[12] In both studies it is not clear what type of metastasisi.e. clinically relevant or notwas additionally detected by IHC.…”
mentioning
confidence: 83%
“…Current guidelines advise routine use of immunohistochemistry (IHC) when ultrastaging SLNs from cervical cancer patients [11]. Immunohistochemistry facilitates detection of micrometastasis and ITC by demonstrating tumor specific proteins, even when these tumor cells are not seen on examination of multiple step sections [3,5,12]. However, the added clinical value of IHCin terms of finding low volume disease that adjusts therapeutic strategyremains uncertain, while its routine use is time-consuming and costly.…”
Section: Introductionmentioning
confidence: 99%
“…Состояние лимфатических узлов (ЛУ) является важнейшим прогностическим фактором при ранней стадии рака шейки матки (РШМ) и основным критерием для назначения адъювантной терапии [3]. В пересмотренной классификации Международной федерации…”
Section: актуальностьunclassified